Post-autotomy limb movement in the porcellanid crab Petrolisthes japonicus. Issue 2 (4th March 2022) - Hamasaki, Katsuyuki; Wachi, Yuuki; Dan, Shigeki
Abstract : Post-autotomy appendage movement has evolved independently in several vertebrate and invertebrate taxa. Moving appendage may divert a predator's attention away from the body, allowing the prey to escape. Decapod crustaceans, particularly anomuran and brachyuran crabs, have been well studied in terms of autotomy; however, no studies have focused on post-autotomy limb behaviour. We first found post-autotomy limb movement in decapod crustaceans using the porcellanid crab Petrolisthes japonicus . Porcellanid crabs possess large chelipeds. The porcellanid crab autotomizes the cheliped readily when a predator crab grasps it by the cheliped, enabling it to escape. Our laboratory observations revealed that autotomized chelipeds of P. japonicus moved voluntarily: they repeated closing and stretching movements of the chela and remaining parts on the propodus-carpus joint. The number of strokes (a single sequential closing and stretching movement) and the total stroke duration of the chelipeds were about 28 times and 17 sec on average, respectively. Post-autotomy cheliped movement may further improve the anti-predator defence efficacy of large chelipeds with a hair-trigger autotomy response in porcellanid crabs.